Cogasification of Coal and Biomass: A Review - J. S. Brar; K. Singh; J. Wang; S. Kumar (International Journal of Forestry Research)
Recently, there has been significant research interest in cogasification of coal and various types of biomass blends to improve biomass gasification by reducing the tar content in the product gas. In addition, ash present in biomass catalyzes the gasification of coal. However, due to the fibrous nature of biomass and the large difference in gasification temperature of coal and biomass, cogasification in existing systems presents technical challenges. This paper documents research studies conducted on the cogasification of various types of coal and biomass using different types of gasifiers under various sets of operating conditions. In addition, the influence of cogasification on upstream and downstream processing is presented.